Keloid Formation in Athletes: Pathophysiology, Biomechanical Risk Factors, Psychosocial Burden, and Current Therapeutic Approaches - Biskup, Alicja; Wnęk, Agata; Smagowska, Julia; Kala - Kaziszyn, Ewa (Quality in Sport, 2026)
Keloids represent a chronic dermatological condition resulting from abnormal wound healing and excessive proliferation of fibrotic tissue. These lesions may lead not only to physical symptoms such as pain, pruritus, and restricted mobility, but also to significant psychosocial consequences that adversely affect patients’ quality of life. In recent years, increasing attention has been directed toward the molecular mechanisms underlying keloid formation, including dysregulation of fibroblast activity, abnormal signaling pathway modulation, and the influence of genetic and biomechanical factors. Athletes constitute a particularly vulnerable group with regard to the development of pathological scars. Intense physical activity, frequent skin injuries, repetitive microtrauma, and surgical procedures commonly performed in sports medicine may increase the risk of keloid formation. Furthermore, scar lesions may negatively affect tissue function, training comfort, physical performance, and the psychological well-being of athletes. The aim of this paper is to present current knowledge regarding the molecular mechanisms involved in keloid formation, biomechanical risk factors observed in athletes, contemporary therapeutic approaches, and the psychosocial consequences of these lesions in the context of sports medicine.